Long-term declines of European insectivorous bird populations and potential causes - Bowler, Diana E; Heldbjerg, Henning; Fox, Anthony D; de Jong, Maaike; Böhning-Gaese, Katrin (Conservation biology, 2019)
Evidence of declines in insect populations has recently received considerable scientific and societal attention. However, the lack of long-term insect monitoring makes it difficult to assess whether declines are geographically widespread. By contrast, bird populations are well monitored and often used as indicators of environmental change. We compared the population trends of European insectivorous birds with those of other birds to assess whether patterns in bird population trends were consistent with declines of insects. We further examined whether declines were evident for insectivores with different habitats, foraging strata, and other ecological preferences. Bird population trends were estimated for Europe (1990-2015) and Denmark (1990-2016). On average, insectivores declined over the study period (13% across Europe and 28% in Denmark), whereas omnivores had stable populations. Seedeaters also declined (28% across Europe; 34% in Denmark), but this assessment was based on fewer species than for other groups. The effects of insectivory were stronger for farmland species (especially grassland species), for ground feeders, and for cold-adapted species. Insectivory was associated with long-distance migration, which was also linked to population declines. However, many insectivores had stable populations, especially habitat generalists. Our findings suggest that the decline of insectivores is primarily associated with agricultural intensification and loss of grassland habitat. The loss of both seed and insect specialists indicates an overall trend toward bird communities dominated by diet generalists.
Keywords: Birds; climate change; population trends; Agriculture; bioindicators; Europe; zvířata; intensificación agrícola; agricultural intensification; ptáci; Population Dynamics; cambio climático; declinaciones de insectos; ekosystém; Ecosystem; bioindicadores; Evropa; tendencias poblacionales; zachování přírodních zdrojů; zemědělství; populační dynamika; Animals; insect declines; Conservation of Natural Resources